2022
DOI: 10.5812/intjssh-128560
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Brazilian Older Adult Women to Join a Community Physical Activity Program Before COVID-19 Pandemic

Abstract: Background: Intrinsic and extrinsic motivational factors can affect the levels of adherence of physical activity (PA) during the aging process. Objectives: Investigate the intrinsic and extrinsic aspects and motivation that led older women to enroll in and adhere to a community PA program before the COVID-19 pandemic. Methods: Data were collected via transversal survey before the COVID-19 pandemic. The sample consisted of 21 women, participants of a PA workshop, aged between 60 to 86 years [< 1-year (n = 8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Though our data are in line with many previous studies, it is hard to establish a causal relationship between pandemic context and mental health disorders in a cross-sectional study. The study might be improved in the future by increasing the correlation analysis between mental health and other factors such as perceived social support, living environment (urban or rural area), physical activity, sedentary time, and dietary behaviors ( Ivbijaro et al, 2021 ; Shibata et al, 2021 ; Rahim et al, 2022 ; Silva et al, 2022 ; Zhao et al, 2022 ). Furthermore, mood disturbance has been reported to be associated with inflammatory processes ( Beurel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though our data are in line with many previous studies, it is hard to establish a causal relationship between pandemic context and mental health disorders in a cross-sectional study. The study might be improved in the future by increasing the correlation analysis between mental health and other factors such as perceived social support, living environment (urban or rural area), physical activity, sedentary time, and dietary behaviors ( Ivbijaro et al, 2021 ; Shibata et al, 2021 ; Rahim et al, 2022 ; Silva et al, 2022 ; Zhao et al, 2022 ). Furthermore, mood disturbance has been reported to be associated with inflammatory processes ( Beurel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with regard to the great benefits of exercise (especially resistance exercises) such as increasing muscle hypertrophy and improving muscle strength, performing regular resistance exercises could be a good strategy to prevent sarcopenia and its harmful effects [ 16 ]. It has been demonstrated that several motivational factors such as worrying about health, the influence of friends and family, and recommendations from a medical professional could help to increase the level of physical activity among older adults that should be noticed [ 17 ]. According to a review article [ 18 ], sedentary older adults are recommended to engage in physical activity with moderate intensity, three to five times a week.…”
Section: Introductionmentioning
confidence: 99%
“…Regular activity especially resistance exercise is essential for healthy aging and offers a range of health benefits [ 7 ], but older people have difficulty achieving or not achieve 150 min of physical activity per week recommended activity level to maintain or improve health-related levels of physical fitness. Therefore, it is crucial to find safe and effective exercise methods and carry out sustainable exercise intervention for older population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%